2022
DOI: 10.3390/app12146958
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL-1A, IL-1B and IL-1RN Polymorphisms and Peri-Implantitis: A Systematic Review and Meta-Analysis

Abstract: Recent studies report that individuals with polymorphisms in the genes that encode for interleukin (IL)-1α and IL-1β (IL-1A and IL1B, respectively) and for IL-1 receptor antagonist (IL-1RN) may be more susceptible in developing peri-implantitis. Therefore, the current systematic review evaluates what is reported about the role of genetics, more specifically of single nucleotide polymorphisms (SNP) on IL-1 and variable number of tandem repeats (VNTR) on IL-1RN, in the development of peri-implantitis. This syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…IL-1β is an important cytokine for the differentiation of Th-17 cells with multiple signaling effects, including RORγt expression [55]. IL-1β is a proinflammatory cytokine that plays a significant role in the immune response and inflammatory processes [56]. IL-1β triggers the production of other cytokines, including IL-6 and IL-23 [57].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is an important cytokine for the differentiation of Th-17 cells with multiple signaling effects, including RORγt expression [55]. IL-1β is a proinflammatory cytokine that plays a significant role in the immune response and inflammatory processes [56]. IL-1β triggers the production of other cytokines, including IL-6 and IL-23 [57].…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is periimplantitis, a growing problem that requires better approaches in terms of prevention and treatment. Cardoso et al [1] carried out a systematic review via a meta-analysis with the aim of evaluating the association between IL-1A, IL-1B and IL-1RN polymorphisms and periimplantitis. The results showed that patients who have the polymorphic allele at position +3954 of the IL-1B gene have on average almost twice the risk of developing peri-implantitis.…”
Section: New Techniques Materials and Technologies In Dentistrymentioning
confidence: 99%
“…Current research avenues are directed towards supplementary, non-invasive techniques, where early detection of pathological biological activities is possible. Furthermore, innovations in implant dentistry have been documented in the quest to reduce morbidity, biological complications, and surgical times [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%